(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2011)
Seventy eight samples of poultry litter were collected from different farm of rural area of Chittagong, Bangladesh. Among 78 samples, 43 samples were Salmonella positive. Twelve organisms those showing resistance against at least two antibiotics were selected (Table I). Antimicrobial activities of the bark extract of T. arjuna against twelve selected isolates of Salmonella were then determined (Table II). Eleven of those selected isolates were shown zone of inhibition against crude bark extract of T. arjuna and one Salmonella (CL-10F) isolates showed no zone of inhibition. Key words: T. arjuna; Salmonella; Poultry; Antibiotic; Resistant; Anti-microbial. DOI: http://dx.doi.org/10.3329/bjsir.v46i2.8180 Bangladesh J. Sci. Ind. Res. 46(2), 147-152, 2011